Effect of wheat flour characteristics on sponge cake quality - Moiraghi, Malena (2012)
BACKGROUND: To select the flour parameters that relate strongly to cake-making performance, in this study the relationship between sponge cake quality, solvent retention capacity (SRC) profile and flour physicochemical characteristics wasinvestigated using 38 soft wheat samples of different origins. Particle size average, protein, damaged starch, water-soluble pentosans, total pentosans, SRC and pasting properties were analysed. Sponge cake volume and crumb texture were measured to evaluate cake quality. Cluster analysis was applied to assess differences in flour quality parameters among wheat lines based on the SRC profile. RESULTS: Cluster 1 showed significantly higher sponge cake volume and crumb softness, finer particle size and lower SRC sucrose, SRC carbonate, SRC water, damaged starch and protein content. Particle size, damaged starch, protein, thickening capacity and SRC parameters correlated negatively with sponge cake volume, while total pentosans and pasting temperature showed the opposite effect. CONCLUSION: The negative correlations between cake volume and SRC parameters along with the cluster analysis results indicated that flours with smaller particle size, lower absorption capacity and higher pasting temperature had better cakemaking performance. Some simple analyses, such as SRC, particle size distribution and pasting properties, may help to choose flours suitable for cake making.